PSA total y su relación con factores que se predisponen al desarrollo de alteraciones prostáticas en policías en servicio pasivo de la ciudad de Loja durante el periodo marzo-julio 2014 - Maza Estrada, Yessenia Paulina (2015)
The most common diseases with adult men are: prostatitis, cancer and benign prostatic hyperplasia; when the last ones are detected at an early stage they can improve the quality of life of people suffering with them, by this reason it is recommended to do the Prostate Specific Antigen (PSA) total and free in older males 40 years annually, this test is sensitive and detects 65% of cases. In developing of these alterations are involved different non-modifiable factors such as advanced age, genetics factors and race, these alterations with modifiable factors contribute to the development of these pathologies. In this research work, it was proposed to quantify serum total PSA, to determine the risk factors that predispose to the development of prostate disorders and to relate risk factors with PSA levels in Policemen of Passive Service of Loja city. This study is descriptive and cross-section, in which 54 samples were analyzed from which the total of PSA was measured by electrochemiluminescence, in this way it was determined that 13% of patients have higher than 4 ng/mL values; between risk factors found through the application of a survey it is emphasize: family history of cancer and benign prostatic hyperplasia 57% alcohol consumption more than 3 times a month 100%; cigarette consumption more than 4 times a week 71%, presence of urinary tract infection 71%, also patients 66-75 years 43% had greater than 4 ng/mL values. It is important to take into account the patient's clinical to relate to possible altered values, obtained during the analysis of the sample and perform other tests such as biopsies or ultrasound, because these tests together generate additional information to help in the diagnosis of the physician. Keywords: total PSA, risk factors, prostate disorders, electrochemiluminescence